Devil's Cub - Heyer, Georgette (Naperville, Ill. : Sourcebooks Casablanca, 2009)
Follow a dashing and wild young nobleman and the gently bred young lady in whom he finally meets his match. As the two become entangled, Mary's reputation and future lie in the hands of Dominic, a devilish rake, who finds her more fascinating every day...
Keywords: Aristocracy (Social class) -- England; Manners and customs; England -- Social life and customs -- 18th century; Regency fiction; Love stories; Historical fiction; Fiction